Lingvosemiotic Content ofLinguistic Features ofThe Speech Genre “Wish” (Global Scientific Review, 2024)
In the article, the linguistic features of the speech genre “wish” in the language system are characterized by socio-semiotic content, which has a religious nature, and the features of its implementation with the content of desire in various social situations